Effect of Multidisciplinary Team Collaborative Nursing Model Combined with Mind Mapping Teaching Method on Postoperative Complications and Mental Health of Patients with Advanced Pancreatic Cancer - Wei Ma; Lan Zhang; Chunxiu Wang; Xiaona Xu (Tehran University of Medical Sciences, 2022)
Background: To analyze the effect of multidisciplinary team (MDT) collaborative nursing model combined with mind mapping teaching method on postoperative complications and mental health of patients with advanced pancreatic cancer (APC). Methods: The clinical data of 100 APC patients treated in Liaoning Cancer Hospital and Institute, Shenyang, China (Dec 2018 - Dec 2020) were retrospectively analyzed. They were randomly and equally split into group J and group Q. The patients of group J were nursed with mind mapping teaching method, while those of group Q were nursed with MDT collaborative nursing model combined with mind mapping teaching method to compare the incidence of complications, quality of life (QOL) and mental health between the two groups after nursing. Results: After nursing, the SAS, SDS and NRS scores decreased in both groups, with the notably lower scores in group Q compared with group J (P < 0.05). After nursing, the QOL scores increased in both groups, with the notably higher scores in group Q compared with group J (P < 0.05). Compared with group J, the nursing satisfaction in group Q was notably higher while the incidence of complications was notably lower (P < 0.05). Conclusion: The MDT collaborative nursing model combined with mind mapping teaching method in postoperative nursing of APC patients can improve negative emotions such as anxiety and depression, enhance the QOL, alleviate pain, reduce the incidence of postoperative complications and improve nursing satisfaction, worthy of application and promotion in clinic.